2017
DOI: 10.11002/kjfp.2017.24.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modified atmosphere packaging (MAP) and vaporized ethyl pyruvate (EP) treatment for the shelf life of‘Seolhyang’strawberries

Abstract: We have studied the technology to extend the storage period of ‘Seolhyang’ strawberries using modified atmosphere package (MAP) and ethyl pyruvate (EP) treatment for domestic distribution and export. The selected ripe strawberries harvested on December 28, 2016 at the Sancheong farmhouse were transported to the laboratory for 2 h and tested. After a day’s precooling at 4℃, the strawberries were divided into seven experimental groups. These groups were control, active MAP using low density polyethylene (LDPE), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…By contrast, the structure of strawberries with active MAP did not change within 2 days of storage, while 50% of the strawberries had softened and waterlogged tissue with mold growth beyond 14 days. According to a report by Kim et al (2017), fungi are the most serious problem in the distribution and export of strawberries, and decreasing mold growth from 36% to <7% using MAP could extend the shelf life. Another study reported an extension of the post-harvest life of strawberries to 14 days without any fungal infection or any change in appearance obtained by combined radiation irradiation with MAP treatment (Jouki & Khazaei, 2014).…”
Section: Rate Of Decay During Storagementioning
confidence: 99%
“…By contrast, the structure of strawberries with active MAP did not change within 2 days of storage, while 50% of the strawberries had softened and waterlogged tissue with mold growth beyond 14 days. According to a report by Kim et al (2017), fungi are the most serious problem in the distribution and export of strawberries, and decreasing mold growth from 36% to <7% using MAP could extend the shelf life. Another study reported an extension of the post-harvest life of strawberries to 14 days without any fungal infection or any change in appearance obtained by combined radiation irradiation with MAP treatment (Jouki & Khazaei, 2014).…”
Section: Rate Of Decay During Storagementioning
confidence: 99%